1992
DOI: 10.1159/000227094
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Intraperitoneal Alpha-2a Interferon

Abstract: Eighteen patients affected with epithelial ovarian cancer have been treated by intraperitoneal α2a-Interferon. The usual single dosage was 54 x 106 U at weekly intervals for four times (eight times in responders): 10 h-istologically confirmed complete remissions and 3 partial remissions have been obtained; the toxicity was represented by fever in the majority of the cases, by abdominal discomfort in some cases, and by a mild transitory neurological complication in 1 case. Seventeen of 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The authors have also investigated the IP delivery of interferons (IFNs) and especially of IFN-a that can be detected in peritoneum more than 24 h after intracavitary instillation due to its large molecular size and that can cause tumor cell kill through both direct cytotoxicity and cell-mediated immune response enhancement (44)(45)(46)(47)(48) . In the early study of Berek et al (45) , weekly IFN-a at escalating doses from 5 to 50 3 10 6 U for 16 weeks achieved a surgically documented complete response in 4 (36%) and a partial response in 1 (9%) of the 11 patients with persistent epithelial ovarian at second look.…”
Section: Ip Chemotherapy As Salvage Treatment For Patients With Persimentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have also investigated the IP delivery of interferons (IFNs) and especially of IFN-a that can be detected in peritoneum more than 24 h after intracavitary instillation due to its large molecular size and that can cause tumor cell kill through both direct cytotoxicity and cell-mediated immune response enhancement (44)(45)(46)(47)(48) . In the early study of Berek et al (45) , weekly IFN-a at escalating doses from 5 to 50 3 10 6 U for 16 weeks achieved a surgically documented complete response in 4 (36%) and a partial response in 1 (9%) of the 11 patients with persistent epithelial ovarian at second look.…”
Section: Ip Chemotherapy As Salvage Treatment For Patients With Persimentioning
confidence: 99%
“…The same authors (48) delivered IP IFN-a at weekly doses 50 3 10 6 U for 12 cycles to patients with less than 0.5-cm residual disease at second look and found a surgically assessed complete and partial response in 16% and 12%, respectively, of the 25 patients with platinum-sensitive disease compared to 0% of the 21 patients with platinum-resistant disease. Nicoletto et al (46) reported ten (55%) surgically documented complete responses and three (17%) partial responses following weekly IP IFN-a at the dose of 54 3 10 6 U for four to eight cycles to 18 patients with persistent epithelial ovarian cancer mainly consisting of microscopic disease. IP IFN-a can be useful for the palliative management of recurrent ascites even in nonovarian gynecological malignancies (49) .…”
Section: Ip Chemotherapy As Salvage Treatment For Patients With Persimentioning
confidence: 99%